Independency And Loyalty Reflected At Jonathan Stroud's The Ring Of Solomon (2010): A Psychoanalytic Approach, - Rahman, Farizky; , Dr. Phil. Dewi Candraningrum, M.Ed; , Siti Fatimah, S. Pd, M. Hum (2014)
This study is about independency and loyalty. The problem of this study is to reveal how independency and loyalty reflected on The Ring of Solomon novel written by Jonathan Stroud which is published in 2010. There are two objectives: the first is to analyze the novel in term of structural elements and the second is to analyze the novel based on Psychoanalytic Approach. The object of the study is The Ring of Solomon novel written by Jonathan Stroud. The research is conducted by using Psychoanalytic Approach. This study belongs to qualitative research. In this research, there are two types of data, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in the The Ring of Solomon novel, Jonathan Stroud successfully shows that the character and characterization, plot, setting, point of view, theme, and style is correlated to each other and form an unity. Second, based on psychoanalytic approach, the result shows that the independency and loyalty is a human being trait that is valuable in achieving goals.